Intestinal Caseous Lymphadenitis in Sheep - Martins, Alexandre Machado; Carneiro, Alexandre Santos; Diniz, Lara Giovana; Dall'Acqua, Priscila Chediek; Bezzerril, Juliana Evangelista; de Souza, Fabricio Eumar; de Paula, Eric Mateus Nascimento; Martini, Andresa de Cássia (Acta Scientiae Veterinariae, 2021)
Background: Caseous Lymphadenitis (CL) is a chronic infectious disease caused by the bacterium Corynebacterium pseudotuberculosis, which is considered the main agent responsible for abscess lesions. In the visceral form it can affect the internal organs of sheep and goats, which could negatively affect animal health and cause large economic losses for producers. Case: This study aims to report a case of intestinal CL in sheep, with suspected diagnosis during physical examination and identification during the performance of the oophorectomy procedure, adopted as a management approach. It is a mixed breed sheep, aged over 5 years; weight 28 kg; emaciated on physical examination; with pale pink and moist eyelid mucosa; heart and respiratory rate: 81 beats/min and 22 movements/min, respectively; body temperature 39.2°C; ruminal movements at 1 movement/min; without identification of lymphadenomegaly on palpation, however, it was observed that the right submandibular lymph node presented tissue retraction compatible with the healing process. For the surgical procedure, an 18-h fast was used and pre-anesthetic medication with 2% xylazine (0.1 mg/kg), 10% ketamine (5 mg/kg) and 50 mg/mL tramadol (2 mg/kg) administrated intramuscularly. The animal was placed in the left lateral decubitus position, then was performed trichotomy and epidural administration of 2% lidocaine (4 mg/kg) and maintenance with propofol 10 mg/mL intravenous dose-effect and oxygen mask 3 liters/min, antibiotic prophylaxis was performed with 10% enrofloxacin (2.5 mg/kg). Flank oophorectomy was performed according to the classic technique and during abdominal inspection, abscess lesions were found in the mesentery and intestinal loops. Incisional biopsy was performed to collect samples in the jejunal segment. At the end of the procedure, 50 mg/mL (2.2 mg/kg) of flunixin meglumine was administered intravenously. A 0.6 cm x 0.2 cm sample, was submitted to histological analysis, which showed the presence of central necrosis areas formed by concentric lamellae, with the presence of large bacterial colonies and foci of mineralization, surrounded by a strip of inflammatory infiltrate with epithelial macrophages and few neutrophils. In the adjacent layer, lymphocytes and plasmocytes were found and the entire lesion was delimited by fibrous conjunctive tissue, compatible with lesions caused by Corynebacterium pseudotuberculosis, the causative agent of CL. During the whole postoperative period the animal was kept isolated from the herd. Due to the unfavorable prognosis and histological confirmation of visceral CL, euthanasia was indicated. The animal was sent for necropsy and no lesions compatible with CL were found in other organs or tissues besides the anatomical structures where the lesions were previously described (intestine and mesentery). Discussion: As it is an infectious disease, isolation and euthanasia should be indicated in cases of CL, in order to not compromise the health of the herd. Thus, justifying the orientation of euthanasia after histological confirmation. The case did not have other possibilities of diagnostic aid, however, histological lesions of CL are characteristic but not pathognomonic, as it could be confused with lesions caused by other pyogenic pathogens. In this way, clinical considerations and complementary exams are relevant to support the diagnostic. To conclude, the observation and physical examination of the herd were fundamental tools for raising the diagnostic hypothesis ante mortem. Complementary tests allowed the confirmation of the disease and prevented the spread in the herd, which could lead to large economic losses for producers and negatively affect animal health.